Pengembangan Kemampuan Motorik Halus Melalui Kegiatan Menganyam - Sri Rejeki; Ika Pribianti; Yurna Devi (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research aims to improve fine motor skills through weaving activities. This research is Classroom Action Research. The research subjects were Group B children with a total of 15 children consisting of 9 boys and 6 girls for the 2020/2021 academic year. The object of this research is fine motor skills. Data collection techniques are carried out using observation and documentation. The tool used is an observation instrument sheet. The data analysis technique was carried out descriptively quantitatively. This research was carried out in two cycles. The results of the research showed that the fine motor skills of Group B children at the Pre-Cycle stage achieved a new percentage of 40.00%, increasing in Cycle I by 52.78% and in Cycle II reaching 72.22% in the Developing According to Expectations (BSH) category. Based on the research results, it can be concluded that weaving activities can improve fine motor skills in children aged 5-6 years at Inayah Kindergarten, Ujungbatu District, Rokan Hulu Regency. Based on the results of the research above, the researcher suggested to teachers to make weaving activities an alternative activity in improving children's fine motor skills Keywords: Fine motor skills, pipette folding activities, classroom action research